PENGARUH LITERASI KEUANGAN SYARIAH DAN PROMOSI TERHADAP KEPUTUSAN NASABAH DALAM MEMILIH PRODUK BANK RIAU KEPRI SYARIAH - Zulmi Randha Nadhea; Suhar; Nurfitri Martaliah (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
Customers' decisions to save are influenced by several internal and external factors such as financial literacy and promotions. Financial literacy reflects an individual's ability to understand financial concepts, financial products, and services and to control personal financial resources independently. Promotion is one of the determining factors for the success of a marketing program. This research aims to determine the influence of sharia financial literacy and promotions both spatially and simultaneously on customers' decisions in choosing Bank Riau Kepri Syariah products. This research approach uses a quantitative descriptive approach. Data was collected using questionnaires and field observations. The research results show that partially sharia financial literacy and promotion have an influence on customers' decisions in choosing Bank Riau Kepri Syariah products. Simultaneously, the variables of sharia financial literacy and promotion influence customers' decisions in choosing Bank Riau Kepri Syariah products with a percentage of 77.3%.